A importância do pensamento pioneiro de Josué de Castro para as políticas sociais no Brasil atual - Gonçalves, Vicente Ferrer Augusto (2011)
It tells the importance of the life, workmanship and contributions of Josué de Castro for the agreement of the brazilian reality. It describes the main workmanships of the author, regarding its conceptions, acts and actions based on ideas of thinkers whom they had searched to awake the reflection of the society and the fight to transform it or to become it more solidary joust and. It emphasizes the aspects of the poverty and hunger in the world. It presents information on the current Public Politics, mentions on the minimum income, I assist it and the objective of the Government in banishing the hunger and the controversial aspects of the adoption of such politics. The methodologic conception of this study was applied by means of a bibliographical research in books, texts and articles, in the direction to demonstrate new abilities to deal with the subject and to deepen the knowledge.